Electroencephalographic changes associated with non-invasive nociceptive stimulus in minimally anaesthetised dogs - Kaka, Ubedullah; Goh, Yong Meng; Chean, Leow Wei; Chen, Hui Cheng (De Gruyter Open, 2016)
Electroencephalography (EEG) has been reported as an objective, non-invasive and stress free technique for nociceptive studies. Electrical stimuli can be used to evaluate the efficacy of centrally acting agents. Peripheral nerve stimulator can be a good and cheap source of electric stimulus for studies of nociception, and studies evaluating analgesic effect of drugs under EEG. In this study suitability of peripheral nerve stimulator, and milliamperage for nociceptive studies under electroencephalography were evaluated. Six dogs were subjected to electric stimulus of 20, 40, 60 and 80 milliamperes (mAs) before and after tramadol administration at 4 mg/kg IV. Electroencephalograph was recorded during electric stimulus prior tramadol (pre-tramadol) and during electric stimulus after tramadol (post-tramadol) under minimal anaesthesia. Anaesthesia was induced with propofol and maintained with halothane at a stable concentration between 0.85 and 0.95%. Pre-tramadol median frequency (MF) increased significantly (p<0.05) at 40, 60 and 80 mAs post-electric stimulus compared to baseline MF. No difference in pre-tramadol MF was observed between 60 and 80 mAs. Tramadol produced significant effect by depression of MF at all intensities. The effect was less evident at 80 mAs. The results revealed that tramadol produced evident effect between 20 and 60 mAs. Thus, it is concluded that nerve stimulator can be used with the current between 20 and 60 mAs for nociceptive studies.